Factors Associated with the Incidence of Anemia among Pregnant Women in Indonesia (IFLS 5 Secondary Data Analysis) - Nurfajriah, Nurfajriah; Azam, Mahalul; Indarjo, Sofwan (Universitas Negeri Semarang, 2024)
Anemia is a severe public health problem with the incidence of anemia among pregnant women in Indonesia at 46.2% based on data from the Indonesia Family Life Survey (IFLS) 5. This study aimed to determine the factors associated with the incidence of anemia among pregnant women in Indonesia. The cross-sectional design of the study was using secondary data from IFLS 5 which was conducted from September 2014 to March 2015 on 292 pregnant women out of 53,160 respondents based on inclusion and exclusion criteria. Chi-square analysis showed that maternal age, maternal occupation, smoking habit, food frequency, green vegetable consumption, vitamin C consumption, socioeconomic status and health service distance were not associated with the incidence of anemia among pregnant women in Indonesia. Whereas maternal education (p=0.006), nutritional status (p=0.003), gestational age (p=0.001), iron consumption (p=0.001), ANC examination (p=0.006) and protein consumption (p=0.012) were associated with the incidence of anemia among pregnant women in Indonesia. Multivariate analysis with multiple logistic regression showed maternal education (p=0.014), nutritional status (p=<0.001), gestational age (p=0.002), iron consumption (p=0.008) and protein consumption (p=0.038) were associated with the incidence of anemia among pregnant women in Indonesia. Gestational age was the most dominant variable associated with the incidence of anemia among pregnant women after controlling for maternal education, nutritional status, iron consumption and protein consumption (OR=3.029; 95% CI=1.520-6.038).